Wound-Healing Potential of Myristica fragrans Essential Oil: A Multi-Targeted Approach Involving Inflammation, Oxidative Stress, and Apoptosis Regulation - Yahya I. Asiri; Krishnaraju Venkatesan (Pharmaceuticals, 2025)
Background: Essential oils are widely studied for their therapeutic potential, including their role in wound healing. Myristica fragrans essential oil (MEO) has been previously investigated for various pharmacological activities, including anti-inflammatory and antimicrobial effects. However, its mechanistic role in accelerating wound healing and modulating critical pathways, such as oxidative stress, inflammation, and apoptosis, remains poorly characterized. MEO contains a rich profile of monoterpene esters, sesquiterpenoids, and phenolic acids, which may contribute to its bioactivity through unique multi-targeted mechanisms. Objective: This research aims to investigate the curative properties of MEO on wound repair, specifically its capacity to regulate inflammation, oxidative stress, and apoptosis in an excision wound model using Wistar rats. Methods: Chemical characterization via GC-MS analysis identified Nitrobenzoate Esters (12.85%), Terpenoid/Cineole (6.99%), and Gamma-Terpinene (4.67%) as the dominant constituents. This study utilized a full-thickness excision wound model, and wound contraction, inflammatory cytokines (IL-1β and TNF-α), a macrophage cell surface marker (CD68), oxidative stress markers (ROS MDA, SOD, GSH), and apoptotic regulation (Caspase-3) was evaluated using macroscopic, histopathological, and immunohistochemical analyses. Result: MEO treatment significantly reduced pro-inflammatory cytokines IL-1β (658.3 ± 32.7 pg/mg, *** p < 0.005) and TNF-α (266.7 ± 33.3 pg/mg, *** p < 0.005), compared to the control group (983.3 ± 60.1 and 650 ± 42.8 ** p < 0.05, respectively). CD68 expression was also markedly decreased (12.67 ± 0.71 ng/mL, *** p < 0.005). Furthermore, MEO effectively attenuated oxidative stress by reducing ROS and MDA levels while restoring antioxidant enzymes GSH and SOD. Conclusions: This study demonstrates that Mace Essential Oil (MEO) effectively promotes wound healing by modulating inflammation, oxidative stress, and apoptosis in a preclinical rat model. Its unique bioactive components suggest significant therapeutic potential as a botanical agent for skin repair. Further research is warranted to explore its application in advanced wound-care formulations.